(untitled) (International Journal of Physiotherapy, 2015)
Background: Parkinson’s Disease (PD) causes increasingly significant disability and functional impairment, negatively influencing the quality of life of those affected by the disease. The tool widely adopted for assessment of quality of life in Parkinson’s disease patients is the Parkinson’s Disease Questionnaire (PDQ- 39). Study objectives: to assess the level of correlation of the PDQ-39 questionnaire with the clinical severity of PD patients; to assess changes in quality of life following home-based rehabilitation treatment. Methods: Thirty patients residing in the province of Naples were enrolled in the study; the inclusion criterion was the presence of Parkinson’s Disease, whilst patients with other neurodegenerative or chronic disorders were excluded. The participants were assessed utilizing: the medical history questionnaire, the Hoehn and Yahr scale to rate disease severity, the PDQ-39. They contemporaneously followed a home-based physiotherapy programme for 18 months. The readings were carried out in three stages: time zero, nine months, eighteen months. Results: The Pearson test indicates a close correlation between clinical severity and quality of life (QoL) ( 0.76 ≤ R ≤ 0.85). Following rehabilitation treatment, the patients reported some improvement in quality of life, particularly in the psychological dimension: the stigma areas and psychological well-being had significantly improved (p < 0.05), whereas the mobility areas and Adl showed only a short-term improvement (p > 0.05). No significant change was found in the areas of cognitive impairment in the Parkinson’s Disease patient. Conclusion: HRQOL strongly correlate with disease progression; home physiotherapy can improve patients condition, especially from emotional point of view.